Anna Hofmann - En sedesam förförerska på varietéscenen - Lagercrantz , Marika V (Tidskrift för genusvetenskap, 1997)
In an analysis of the d i f f e r e n t p e r f o r m a n c e s by Anna Hofman during the f890's Lagercrantz discusses how m o d e r n social distinctions were enacted through an intricate interplay between male gaze and female power. T h e subculture of the vaudeville created space for female e n t r e p r e n e u r s , where a skilful actress like H o f m a n could make use of male desire without getting caught in patriarchal hierarchy.